On Some Challenges Faced by the Judicial Power in the Russian Federation - SVIRIN, Yury Alexandrovich; GUREEV, Vladimir Aleksandrovich; MOKHOV, Alexandr Anatolievich; INOGAMOVA-KHEGAI, Liudmila Valentinovna; SHESTOV, Sergej Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).39, 2020)
The article studies the challenges faced by the judicial branch of the Russian Federation. The avalanche of legal cases has reduced the quality of judicial acts and undermined the objective resolution of legal conflicts. In 2018, the Russian legislator attempted to reform judicial proceedings and introduced extrajudicial proceedings but there are still many unresolved issues that will be addressed in this article. The authors believe that the problems experienced by the judicial branch are caused by the imperfection of the current legislation, as well as economic and political grounds. Without dwelling on political foundations, the article reveals economic and legal causes of such problems. The authors used the methods of synthesis, comparative, structural-functional and statistical analysis, as well as interviewing. The study aims at determining negative causes that delay court hearings and result in unlawful and unjustified judicial acts. The authors have revealed causes for the unsatisfactory performance of the judicial branch in the Russian Federation and proposed certain ways to address these causes. They have also drawn the following conclusion: the separation of powers into three branches (the legislative, executive and judicial branches) in the modern world is outdated since the fourth power has already emerged in many states. Sometimes the so-called presidential branch becomes superior to the first two types and affects the judicial one.